Satisfaction with pain management and impact of pain on quality of life in cancer patients. Issue 2 (17th October 2018) - Lin, Johnson; Hsieh, Ruey‐Kuen; Chen, Jen‐Shi; Lee, Kuan‐Der; Rau, Kun‐Ming; Shao, Yu‐Yun; Sung, Yung‐Chuan; Yeh, Su‐Peng; Chang, Cheng‐Shyong; Liu, Ta‐Chih; Wu, Ming‐Fang; Lee, Ming‐Yang; et al.
Abstract: Aim: To evaluate the prevalence of pain in cancer outpatients in Taiwan and to investigate the impact of pain on quality of life (QoL) and patient satisfaction. Results were compared to those of a similarly designed study conducted in 2008 to identify trends. Methods: Adult patients with cancer treated as outpatients in hospitals throughout Taiwan were recruited. Pain intensity and the extent to which pain interfered with QoL were self‐reported using a modified version of the Brief Pain Inventory. Patients also indicated their level of satisfaction with their physician, as well as with their pain control. Results: A total of 2652 patients were enrolled from 16 sites. Of these, 1167 (44.0%) patients reported experiencing pain during the previous week. Prevalence and severity of pain were highest in patients with progressive disease. A higher pain severity score was significantly associated with greater interference in both physical and psychological functions. Overall, 86.0% of all participants expressed satisfaction with their physician and 84.8% were satisfied with their pain control; satisfaction rates were associated with pain severity. Compared with the findings from the 2008 study, pain prevalence was notably lower and patient satisfaction was significantly greater in the current study. Conclusions: Prevalence and severity of pain were associated with disease stage. Pain interference on QoL correlated significantly with pain severity. Treatment of pain in cancer patients in Taiwan seems to have improved from 2008 to 2014, possibly attributable to new cancer pain treatment guidelines and the wider availability of novel analgesic therapies.